Oral health status and treatment needs of children with sickle cell disease in Abha and Khamis Mushait cities of southern Saudi Arabia - Alamri, Maha H.; Alqahtani, Reem A.; Alqahtani, Norah A.; Shobeili, Wejdan A.; Togoo, Rafi A.; M., Zakirulla (International Journal of Research in Medical Sciences, 2018)
Background: This study aimed to assess the oral health status and dental treatment needs of children with Sickle Cell disease (SCD) in Abha and Khamis Mushait cities of southern Saudi Arabia. Methods: A total of 82 children were included in the study, 41 children with SCD and 41 control group. A total of 82 children having age group of 2 to 13 years from Abha and Khamis Mushait cities of southern Saudi Arabia were examined. The clinical examinations were performed by experienced clinicians in those children who fulfilled the required inclusion criteria. Intraoral examination was done using Decayed-Missing-Filled Teeth Index (DMFT Index) and other dental conditions were examined. Statistical analysis was done with Chi square test and level of significance was set at p<0.05. Results: Prevalence of dental caries was shown between the 2 groups of children i.e., SCD and control. When SCD was compared with control group, the Mean ±Standard deviation for decayed missing filled tooth was found to be DMFT= 6.95±4.79, 8.02±4.33 respectively. Statistically no significant difference was found (P=0.290). 17.1% of children with SCD group has gingivitis compared to control group which is 7.3%. Statistically no significant difference was found (P=0.177). Dental trauma, deleterious oral habits and tooth brushing amount SCD children were shown no statistically significant compared to control group. Conclusions: In the present study no significant difference was evident in dental diseases and treatment needs among SCD and Control group.